Analisis Berpikir Kritis Matematis Siswa dalam Menyelesaikan Masalah Perbandingan - Yuliana Trisanti; Hairus Saleh; Amin, Musfiqul (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This study aims to analyze students' critical thinking skills in solving problems in terms of students' high and medium initial abilities by using four indicators of critical thinking. The processed data is the result of students' critical thinking skills by using initial ability test questions for subject selection and critical thinking ability tests. The questions used to measure critical thinking skills are in the form of essay questions totaling 2 points on comparative material. Based on the processed data, subjects with high initial ability were able to answer 1 question and were able to fulfill 4 indicators of critical thinking. Based on test results and interviews with subjects with high initial ability from 1 question answered, it can be analyzed that for question number 1 part a, students are able to fulfill 4 indicators of critical thinking. For question number 1 part b, students are able to fulfill 4 indicators repeatedly by being able to explain the questions correctly and precisely. subjects with moderate initial abilities were able to answer 1 question only able to fulfill 3 indicators of critical thinking. Based on the results of interviews with subjects with moderate initial ability from 1 question answered it can be analyzed that for question number 1 part a, students are able to fulfill 3 indicators namely interpretation, analysis, evaluation, where. students are able to explain the results of their tests in interviews with answers that are the same as the results of the test.